2018
DOI: 10.1063/1.5020614
|View full text |Cite
|
Sign up to set email alerts
|

Carbon doping induced Ge local structure change in as-deposited Ge2Sb2Te5 film by EXAFS and Raman spectrum

Abstract: The local structure change of Ge induced by carbon doping in as-deposited Ge2Sb2Te5 films were studied by extended X-ray absorption fine structure and Raman spectrum. Ge-C bonds are formed at the expense of reducing the coordination of Ge-Ge and Ge-Te bonds, and make the local structure of Ge to be a well-defined tetrahedral geometry, which increases the rigidity of amorphous network and reduces the number of ABAB rings, thus the crystallization temperature of carbon-doped Ge2Sb2Te5 (CGST) films are enhanced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 33 publications
1
29
1
Order By: Relevance
“…One method to solve the problems is through doping other elements inside the GST material. A variety of elements such as C [98,99], O [100], N [100], Ni [101], Si [102], Al [103,104], Ti [105], W [52] and Cu [106] have been used to improve the device performance.…”
Section: Dopingmentioning
confidence: 99%
“…One method to solve the problems is through doping other elements inside the GST material. A variety of elements such as C [98,99], O [100], N [100], Ni [101], Si [102], Al [103,104], Ti [105], W [52] and Cu [106] have been used to improve the device performance.…”
Section: Dopingmentioning
confidence: 99%
“…The thermal stability of GST is a critical issue for reliable device operation. Several studies on the switching characteristics of GST using various metallic [10][11][12] and nonmetallic element dopants, [13][14][15][16] such as Al, Ag, N, and C, have been reported. With regard to covalent nitrogen doping into Ge-Sb-Te (GST), variations in the electronic structure and chemical bonding 13 characteristics critically affect the thermal stability and phase-change process of GST.…”
Section: Introductionmentioning
confidence: 99%
“…In another case of highly C-doped GST (CGST > $18%), C-C chains signicantly altered the amorphous structure by disordering the Ge-Te tetrahedral network. [14][15][16] Therefore, the fraction of the tetrahedral local structure can be successfully increased, resulting in an increase in electrical resistance and a hindrance in electrical switching capability. 17 However, the dependence of the device characteristics on the programming pulse showed that the crystallization switching speed and resistance ratio were signicantly degraded when the C content exceeded 10%, while the reset power and structural stability of CGST were enhanced by the notable change in thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Such a huge resistance contrast between a-and f-phase is utilized to realize information storage in GST based PCRAM devices 11,12 . If f-phase material was overheated, for example, 320-350°C, it will transform into stable trigonal structure (P3m1, a-b-c stacking sequence feature of (0001) planes) with a further resistance decreasing, which was often indexed with hexagonal (h-) phase (a = 4.20 Å, c = 16.96 Å) 10,13 .…”
mentioning
confidence: 99%